2021
DOI: 10.1089/mdr.2020.0431
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Diversity of Phages, Microbial Taxa, and Antibiotic Resistance Genes in the Sediments of the River Ganges Through Metagenomic Approach

Abstract: In this study, we have analyzed the metagenomic DNA from the pooled sediment sample of the river Ganges to explore the abundance and diversity of phages, microbial community, and antibiotic resistance genes (ARGs). Utilizing data from Illumina platform, 4,174 (*0.0013%) reads were classified for the 285 different DNA viruses largely dominated by the group of 260 distinctive phages (3,602 reads, *86.3%). Among all, Microcystis (782 hits), Haemophilus (403), Synechococcus (386), Pseudomonas (279), Enterococcus (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 105 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…A recent metagenomic study explored the viral habitats of Ganges, focusing primarily on phage identification and assessment of their diversity. It provided insights into the abundance and diversity of phages, microbial communities, and antibiotic resistance genes in river sediment [11]. Very little is known about the types of microbes that are prevalent in freshwater habitats, except species from the division cyanobacteria, which are rather suitable for cultivation and morphological differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent metagenomic study explored the viral habitats of Ganges, focusing primarily on phage identification and assessment of their diversity. It provided insights into the abundance and diversity of phages, microbial communities, and antibiotic resistance genes in river sediment [11]. Very little is known about the types of microbes that are prevalent in freshwater habitats, except species from the division cyanobacteria, which are rather suitable for cultivation and morphological differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research utilizing advanced metagenomic approaches has begun to unveil a bacterial population capable of bioremediating significant contaminants in the river's sediments [5,[14][15][16]. A handful of studies have also employed metagenomic techniques to explore the presence of antibiotic resistance genes in the water and sediments of the Ganga [4,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the comparative study with control Rivers Yamuna and Narmada, pathogenic bacteriophages were found lesser in numbers than pathogenic bacterial species in both Rivers compared to River Ganga" [11]. The Institute of Microbial Technology has reported a variety of different phages having specific bactericidal activity against clinical isolates and pathogens Microcystis, Haemophilus, Synechococcus, Pseudomonas, Enterococcus, Bacillus, Rhodococcus, Caulobacter, Salmonella, Enterobacteria, and Mycobacterium [12]. These studies give us a reason to explore the use of phages in Ganga water for immunomodulating, prophylactic, and therapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%